2017
DOI: 10.1186/s40478-017-0469-x
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent changes in synaptic plasticity enhance tau oligomerization in the mouse hippocampus

Abstract: The aggregation mechanism of phosphorylated tau is an important therapeutic target for tauopathies, including Alzheimer’s disease, although the mechanism by which aggregation occurs is still unknown. Because the phosphorylation process of tau is involved in the trafficking of AMPA receptors, which accompanies the long-term depression (LTD) of synapses, we examined the effect of LTD-inducing low-frequency stimulation (LFS) on the formation of pathological tau aggregates in adult and aged wild-type mice. Our bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 54 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…Disruptions of synaptic plasticity as a result of impaired signaling drive cognitive declines typical of brain aging ( Magnusson et al, 2010 ; Haxaire et al, 2012 ; Morrison and Baxter, 2012 ). While these neuronal signatures are known to occur even in non-pathological aging, they are also typical of major neurodegenerative disorders such as Parkinson’s disease and Alzheimer’s disease ( Silvestri and Camaschella, 2008 ; Thomsen et al, 2015 ; Foster et al, 2017 ; Grimm and Eckert, 2017 ; Kimura et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Disruptions of synaptic plasticity as a result of impaired signaling drive cognitive declines typical of brain aging ( Magnusson et al, 2010 ; Haxaire et al, 2012 ; Morrison and Baxter, 2012 ). While these neuronal signatures are known to occur even in non-pathological aging, they are also typical of major neurodegenerative disorders such as Parkinson’s disease and Alzheimer’s disease ( Silvestri and Camaschella, 2008 ; Thomsen et al, 2015 ; Foster et al, 2017 ; Grimm and Eckert, 2017 ; Kimura et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…As further evidence that autophagy plays a specialized role in the healthy synapse, synaptic activity can reciprocally regulate autophagic activity, especially through neuronal electrical activity [ 90, 94, 101, 105, 107, 110, 111 ]. Additionally, training on memory-related tasks leads to region-specific increases in markers of autophagic activity, which localize to the brain region necessary for learning of the task [ 79 ].…”
Section: Synaptic Autophagy and Cognitive Declinementioning
confidence: 99%
“… The interplay between autophagy and synaptic activity. In the normal cell, autophagy is both modulated by [ 90, 94, 101, 105, 107, 110, 111 ] and modulates [ 79, 86, 89, 91 ] synaptic activity to fine-tune synaptic function. Theoretically, autophagic activity can therefore be up or down regulated to either increase or decrease the amount of synaptic protein turnover.…”
Section: Synaptic Autophagy and Cognitive Declinementioning
confidence: 99%
“…Interestingly these studies found that tau-mediated inhibition of LTD is independent of mGluR5 but depends on GluN2B subunits. LTD-inducing stimulation protocols enhance tau oligomerization in an age-dependent fashion (Kimura et al, 2017) and tau phosphorylation is necessary for induction of LTD (Kimura et al, 2014b;Regan et al, 2015).…”
Section: Tau As a Register Of Established Long-term Plasticitymentioning
confidence: 99%